The Effect Of Motivation, Discipline And Work Stress On Employee Performance At PT. Sumber Abadi Bersama (Sab) - Fatoni, Hamdan Arif (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to determine whether motivation, work discipline, and job stress influence employee performance at PT Sumber Abadi Bersama. The research employed a survey method, and data were collected through questionnaires distributed to 74 respondents who are employees of PT Sumber Abadi Bersama. This study uses a quantitative approach, with the sampling technique based on saturated sampling. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that motivation has a significant effect on employee performance. Work discipline also has a significant effect on employee performance, and job stress likewise shows a significant effect on employee performance. Furthermore, motivation, work discipline, and job stress simultaneously have a significant influence on employee performance at PT Sumber Abadi Bersama.